Perfil sorológico contra o vírus da Febre Amarela (YFV) em uma população de área de risco do estado de Minas Gerais - Ana Gabriella Stoffella Dutra (2019)
The family Flaviviridae comprises RNA viruses, with many representatives considered pathogens of medical and veterinary importance. The genus Flavivirus is the largest in the family and includes Yellow fever virus (YFV). YFV is transmitted to humans and non-human primates by mosquitoes of the genera Haemagogus, Sabethes and Aedes. The Yellow Fever (YF) is an acute febrile illness that can cause severe and fatal conditions. YV is endemic in Africa and South America, and causes recurrent epidemics in these regions. The main preventive measure is through vaccination. This study aimed to evaluate the serological profile against YFV in a rural and urban population of an area at risk for YF and in patients with clinical suspicion of arboviruses coming from the city of Diamantina. The city of Serro was chosen because of the history of cases of YF, as well as the fact that it is located in the current area with permanent recommendation of vaccination against YF and due to previous studies of the group of ecology of emerging viruses in the area. In order to achieve this goal, 632 human serum samples from this study were submitted to plaque reduction serum neutralization (PRNT) assay, which is gold standard for the diagnosis of flavivirus infections. The rural and urban populations of the Serro were evaluated separately and were considered two cut-offs for the technique. A seroprevalence of neutralizing anti-YFV antibodies of 75,2% in the PRNT50 and 34,8% in the PRNT90 was detected in the rural population, whereas 73,5% in the PRNT50 and 30,6% in the PRNT90 was detected in the urban population. For patients from Diamantina, seroprevalence was 72,5% in PRNT50 and 35,3% in PRNT90. Due to the cross reactivity into the genus Flavivirus the serum samples were also tested for the presence of Dengue antibodies. A total of 6,3% of samples tested positive for IgG antibodies and 2,5% tested positive for IgM antibodies by rapid immunochromatographic test and 10,7% were positive for DENV-1 by IgG ELISA. This study reinforces the importance of research that look for elucidate the seroprevalence of neutralizing antibodies to YF in populations at risk. In addition to helping to track susceptible individuals and alert to surveillance and prevention actions in these areas.